EFEKTIVITAS PENERAPAN PERATURAN PEMERINTAH NO.23 TAHUN 2018 TERHADAP TINGKAT PERTUMBUHAN WAJIB PAJAK DAN PENERIMAAN PPh FINAL PADA KPP PRATAMA MANADO - Suci, Tri Sukma Melati; Karamoy, Herman; Rondonuwu, Sintje (GOING CONCERN : JURNAL RISET AKUNTANSI, 2019)
Government Regulation No. 23 Year 2018 (PP 23/2018) is form of tax reform by government as an effort to encourage voluntary tax compliance. PP 23/2018 published on July 1, 2018. The publishing of PP 23/2018 aims to provide convenience, fairness, and simplification of taxation for SMEs taxpayers by cutting the tax rate to 0.5% on turnover or gross sales that don’t exceed Rp 4,8 billions a year. This study aims to determine the growth of taxpayers registered before and after the regulation has been adopted, effectiveness of SMEs tax revenue based on PP 23/2018, and to explain the contribution of the implementation of PP 23/2018 to the revenue of PPh Article 4 Paragraph (2) in the region of KPP Pratama Manado. This research uses a descriptive method. Study result based on the average growth of taxpayers during the 13 months before and after the application, showed that growth of 0.02% taxpayers, while the effectiveness of SMEs tax revenue is less effective and the contribution of PPh PP 23/2018 on PPh Article 4 Paragraph (2) for 13 months since the implementation of PP 23/2018 it was 7,04% with very less criteria. In the future, the government, especially KPP Pratama Manado should be more active in exploring the potential of tax revenue and must continue to conduct direct socialization with a personal approach to the taxpayers.